Positive electrode active material and lithium secondary battery including the same
Patent Information
- Application Number
- CN202180067292.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-10-28
- Filing Date
- 2021-11-08
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2041-11-08
AI Technical Summary
[0012]为了解决上述问题,有通过调节OLO的粒子尺寸或涂敷OLO的表面等粒子的结构改善和表面改质来解决OLO的问题的尝试,但还达不到商业化水平
[0034]根据本发明,可以改善与商用化的其他类型的正极活性物质相比在电化学特性和/或稳定性方面存在劣势的现有的富锂锂锰基氧化物的局限性。
Smart Images

Figure CN116250101B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a positive electrode active material and a lithium secondary battery including the same, and more specifically, to a positive electrode active material and a lithium secondary battery including the same, namely, a lithium-rich lithium manganese-based oxide comprising at least lithium, nickel, manganese and a doped metal, wherein the concentration of the transition metal in the lithium manganese-based oxide is controlled in each region to mitigate and / or prevent the decrease in stability caused by the excessive presence of lithium and manganese in the lithium manganese-based oxide. Background Technology
[0002] Batteries use materials capable of electrochemical reactions at the positive and negative electrodes to store electrical energy. As a representative example of such batteries, there are lithium-ion secondary batteries that store electrical energy through the difference in chemical potential during the insertion / extraction of lithium ions at the positive and negative electrodes.
[0003] The aforementioned lithium secondary battery is prepared by using materials capable of reversible lithium-ion insertion / extraction as positive and negative electrode active materials, and filling the space between the positive and negative electrodes with organic or polymer electrolytes.
[0004] As positive electrode active materials for lithium secondary batteries, lithium composite oxides are being used as examples, and LiCoO2, LiMn2O4, LiNiO2, LiMnO2, or composite oxides of nickel, cobalt, manganese, or aluminum as shown in Korean Patent Publication No. 10-2015-0069334 (publication date: June 23, 2015) are being studied.
[0005] Among the aforementioned positive electrode active materials, LiCoO2 is the most widely used due to its excellent lifetime characteristics and charge / discharge efficiency. However, due to the limited resources of cobalt used as a raw material, its price is expensive, thus limiting its price competitiveness.
[0006] Lithium manganese oxides such as LiMnO2 and LiMn2O4 have the advantages of excellent thermal stability and low price, but they suffer from small capacity and poor high-temperature performance. In addition, LiNiO2-type cathode active materials exhibit high discharge capacity battery characteristics, but they are difficult to synthesize due to the problem of cation mixing between lithium and transition metals, resulting in significant problems in rate performance.
[0007] Furthermore, depending on the severity of this cation mixing, a large amount of lithium byproducts are generated. Most of these byproducts consist of compounds of LiOH and Li₂CO₃. Therefore, they can lead to gelation during the preparation of the cathode slurry, or become a source of gas generation due to repeated charge-discharge cycles after electrode fabrication. In addition, residual Li₂CO₃ increases monomer swelling, thus reducing battery life and causing battery expansion.
[0008] Various candidate materials are being discussed to overcome the shortcomings of these existing positive electrode active materials.
[0009] For example, research is underway on using lithium-rich manganese-based oxides, which contain excess manganese in transition metals and have a lithium content greater than the sum of the transition metal contents, as positive electrode active materials for lithium secondary batteries. These lithium-rich manganese-based oxides are also known as overlithiated layered oxides (OLO).
[0010] While the aforementioned OLO (Oxide Lobe) theoretically offers the advantage of high capacity under high-voltage operating conditions, in practice, due to the excessive manganese content in the oxide, its conductivity is relatively low. Therefore, lithium-ion batteries using OLO suffer from a lower rate capability. As mentioned above, when the rate capability is low, the charge / discharge capacity and lifetime efficiency (cycle capacity retention) deteriorate during the cycling process of the lithium-ion battery.
[0011] Furthermore, during the cycling of lithium secondary batteries using OLO, the decrease in charge / discharge capacity or voltage decay may be caused by phase transitions resulting from the movement of transition metals in lithium manganese-based oxides. For example, when a transition metal in a lithium manganese-based oxide with a layered crystal structure moves in an unexpected direction and triggers a phase transition, spinel or similar crystal structures appear entirely and / or partially in the lithium manganese-based oxide.
[0012] To address the aforementioned issues, attempts have been made to improve the structure and surface of OLO particles by adjusting their size or coating them with OLO, but these efforts have not yet reached a commercial level. Summary of the Invention
[0013] Technical issues
[0014] In the lithium secondary battery market, the growth of lithium secondary batteries for electric vehicles plays a leading role, while the demand for positive electrode active materials used in lithium secondary batteries is constantly changing.
[0015] For example, lithium secondary batteries utilizing LFPs were previously the primary choice from a safety perspective. However, recently, the use of nickel-based lithium composite oxides, which have a higher energy capacity per unit weight compared to LFPs, has been expanded.
[0016] Furthermore, most nickel-based lithium composite oxides used as positive electrode active materials in high-capacity lithium secondary batteries recently require the use of ternary metal elements such as nickel, cobalt and manganese or nickel, cobalt and aluminum. In the case of cobalt, not only is the supply and demand unstable, but the price is also too high compared with other raw materials. Therefore, a new positive electrode active material with a composition that can reduce the cobalt content or eliminate cobalt is needed.
[0017] Therefore, lithium-rich lithium manganese-based oxides can meet the above market expectations, but the electrochemical properties and stability of lithium manganese-based oxides are still insufficient to replace commercially available NCM or NCA type positive electrode active materials.
[0018] However, the inventors of this invention have confirmed that, even though existing lithium-rich manganese-based oxides have disadvantages in electrochemical properties and / or stability compared to other commercially available types of positive electrode active materials, lithium-rich manganese-based oxides can still achieve commercially viable levels of electrochemical properties and stability when the concentration of transition metals in the lithium manganese-based oxides can be controlled in each region.
[0019] Therefore, the object of the present invention is to provide a positive electrode active material comprising a lithium-rich lithium manganese-based oxide containing at least lithium, nickel, manganese and doped metals, wherein the concentration of transition metals in the lithium manganese-based oxide is controlled in each region to reduce and / or prevent the decrease in stability caused by the excessive presence of lithium and manganese in the lithium manganese-based oxide.
[0020] Furthermore, the present invention aims to provide a lithium secondary battery that improves the low-rate characteristics of existing OLOs by using a positive electrode comprising a positive electrode active material as defined herein.
[0021] Solution to the problem
[0022] According to one aspect of the present invention for solving the above-mentioned technical problems, a positive electrode active material is provided, wherein the positive electrode active material is a lithium-rich lithium manganese-based oxide comprising at least lithium, nickel, and manganese, wherein the molar number of all metal elements in the lithium manganese-based oxide is M. 1 The number of moles of nickel is M. 2 At that time, M is calculated from the average composition of all metal elements in the core of the aforementioned lithium manganese-based oxide. 2 / M 1 M, calculated from the average composition of all metallic elements in the shell of the aforementioned lithium manganese-based oxides. 2 / M 1 They are different from each other.
[0023] The aforementioned lithium manganese-based oxide can be represented by the following chemical formula 1.
[0024] [Chemical Formula 1]
[0025] rLi₂MnO₃·(1-r)Li a Ni x Co y Mn z M1 1-(x+y+z) O2
[0026] Wherein, M1 is at least one selected from Mo, Nb, Fe, Cr, V, Cu, Zn, Sn, Mg, Ru, Al, Ti, Zr, B, Na, K, Y, P, Ba, Sr, La, Ga, Gd, Sm, W, Ca, Ce, Ta, Sc, In, S, Ge, Si, and Bi, 0 <r≤0.7,0<a≤1,0<x≤1,0≤y<1,0<z<1,0<x+y+z≤1。
[0027] The lithium manganese-based oxide represented by the above chemical formula 1 may optionally include cobalt. Furthermore, when the above lithium manganese-based oxide includes cobalt, the ratio of the molar amount of cobalt to the molar amount of all metal elements in the above lithium manganese-based oxide may be 10% or less, preferably 5% or less.
[0028] In one embodiment, the aforementioned lithium manganese-based oxide can be a secondary particle comprising at least one primary particle. In this case, M is calculated from the average composition of all metal elements in the nucleus of the aforementioned primary particle. 2 / M 1 (or M) 3 / M 1 ) and M calculated from the average composition of all metallic elements in the shell of the aforementioned primary particle. 2 / M 1 (or M) 3 / M 1 They can differ from each other. In other cases, M is calculated from the average composition of all metallic elements in the nucleus of the aforementioned secondary particles. 2 / M 1 (or M) 3 / M 1 ) and M calculated from the average composition of all metallic elements in the shell of the aforementioned secondary particles. 2 / M 1 (or M) 3 / M 1 They can be different from each other.
[0029] In another embodiment, the lithium manganese-based oxide described above can be a secondary particle comprising at least one primary particle, wherein the primary particle can comprise at least one microcrystal. In this case, M is calculated from the average composition of all metal elements in the core of the microcrystal. 2 / M 1 (or M) 3 / M 1 ) and M calculated from the average composition of all metallic elements in the shell of the aforementioned microcrystals. 2 / M 1 (or M) 3 / M 1 They can be different from each other.
[0030] As shown in the various embodiments above, when the concentrations of any metal elements present in the shell and core of a particle (where the particle can be any microcrystal present in a primary particle, any primary particle present in a secondary particle, or a secondary particle) are different, the particle can be referred to as a core-shell particle. That is, the lithium manganese-based oxide is a core-shell particle, and the average composition of all metal elements constituting the lithium manganese-based oxide in the core and the shell can be different.
[0031] Furthermore, according to another aspect of the present invention, a positive electrode comprising the above-described positive electrode active material is provided.
[0032] Furthermore, according to another aspect of the present invention, a lithium secondary battery using the above-described positive electrode is provided.
[0033] The effects of the invention
[0034] According to the present invention, the limitations of existing lithium-rich lithium manganese-based oxides, which are inferior in terms of electrochemical properties and / or stability compared with other types of commercially available positive electrode active materials, can be overcome.
[0035] Specifically, according to the present invention, there is an advantage that by controlling the concentration of transition metals (especially nickel and doped metals) contained in the lithium-rich lithium manganese-based oxide in each region, it is possible to mitigate and / or prevent the decrease in stability caused by the excessive presence of lithium and manganese in the above-mentioned lithium manganese-based oxide.
[0036] Furthermore, according to the present invention, by controlling the concentration of transition metals (especially nickel and doped metals) contained in lithium-rich manganese-based oxides in each region, the lithium-ion charge transfer and / or diffusion hindered by excess manganese on the particle surface is mitigated, thereby enabling the low conductivity of lithium manganese-based oxides to be improved to a commercially viable level.
[0037] Furthermore, according to the present invention, a concentration gradient of transition metal is formed between the core and shell of the lithium manganese-based oxide, and abrupt changes in the concentration of transition metal in the particles are prevented, thereby improving the stability of the crystal structure of the lithium manganese-based oxide. Attached Figure Description
[0038] Figure 1 To illustrate the distribution of nickel, manganese, and tungsten elements, EDS mapping was performed on the cross-section of the lithium manganese-based oxide contained in the positive electrode active material according to Example 1, based on a cross-sectional TEM image of the lithium manganese-based oxide.
[0039] Figure 2 In order to pass through Figure 1 EDS analysis was performed on the marked directions in the cross-sectional TEM image to show the curves (line sum spectrum) of the changes in the content of metal elements (nickel, manganese and tungsten) present in lithium manganese-based oxides.
[0040] Figure 3 To illustrate the distribution of nickel, cobalt, and manganese elements, EDS mapping was performed on the cross-section of the lithium manganese-based oxide contained in the positive electrode active material according to Example 2, based on the cross-sectional TEM image of the lithium manganese-based oxide.
[0041] Figure 4 In order to pass through Figure 3 EDS analysis was performed on the marked directions in the cross-sectional TEM image to show the curves (line sum spectrum) of the changes in the content of metal elements (nickel, cobalt and manganese) present in lithium manganese-based oxides.
[0042] Figure 5 Based on the cross-sectional TEM image of the lithium manganese-based oxide contained in the positive electrode active material of Example 3, the distribution of nickel, cobalt, manganese and tungsten elements was shown by performing EDS mapping on the cross-section of the lithium manganese-based oxide.
[0043] Figure 6 In order to pass through Figure 5 EDS analysis was performed on the marked directions in the cross-sectional TEM image to show the curves (line sum spectrum) of the changes in the content of metal elements (nickel, cobalt, manganese and tungsten) present in lithium manganese-based oxides.
[0044] Figure 7 Based on the cross-sectional TEM image of the lithium manganese-based oxide contained in the positive electrode active material of Example 8, the distribution of nickel, cobalt and manganese elements was shown by performing EDS mapping on the cross-section of the lithium manganese-based oxide.
[0045] Figure 8 In order to pass through Figure 7The direction marked ① in the cross-sectional TEM image was subjected to EDS analysis to show the curve (line sum spectrum) of the changes in the content of metal elements (nickel, cobalt and manganese) present in lithium manganese-based oxides.
[0046] Figure 9 In order to pass through Figure 7 The direction marked in the cross-sectional TEM image ② was used for EDS analysis to show the curve (line sum spectrum) of the changes in the content of metal elements (nickel, cobalt and manganese) present in lithium manganese-based oxides.
[0047] Figure 10 The distribution of nickel and manganese elements was shown by performing EDS mapping on the cross-section of the lithium manganese-based oxide contained in the positive electrode active material of Comparative Example 1 using a cross-sectional TEM image.
[0048] Figure 11 In order to pass through Figure 10 EDS analysis was performed on the marked directions in the cross-sectional TEM image to show the curves (line sum spectrum) of the changes in the content of metal elements (nickel and manganese) present in lithium manganese-based oxides. Detailed Implementation
[0049] Specific terms are defined herein for ease of understanding. Unless specifically defined herein, scientific and technical terms used herein should have the meanings commonly understood by those skilled in the art. Furthermore, it should be understood that, as used herein, the singular form is intended to include the plural form, and vice versa, unless the context clearly indicates otherwise.
[0050] The present invention will be described in more detail below, comprising a positive electrode active material including at least lithium, nickel, manganese and doped metals, a lithium-rich lithium manganese-based oxide, and a lithium secondary battery comprising the above-mentioned positive electrode active material.
[0051] Positive electrode active material
[0052] According to one aspect of the present invention, a positive electrode active material comprising a lithium-rich lithium manganese-based oxide containing at least lithium, nickel, manganese, and a doped metal is provided. The aforementioned lithium manganese-based oxide is a composite metal oxide capable of intercalating and deintercalating lithium ions.
[0053] The lithium manganese-based oxide contained in the positive electrode active material as defined herein may be a secondary particle containing at least one primary particle.
[0054] Here, "secondary particles including at least one primary particle" should be understood as including "particles formed by the condensation of multiple primary particles" or "non-condensed forms of particles including a single primary particle".
[0055] The primary particles and / or secondary particles described above can each independently have a rod-shaped, elliptical, and / or irregular shape. Therefore, when the average major axis length is used as a size indicator for the primary and secondary particles, the average major axis length of the primary particles constituting the lithium manganese-based oxide can be from 0.1 μm to 5 μm, and the average major axis length of the secondary particles can be from 1 μm to 30 μm. The average major axis length of the secondary particles can vary depending on the number of primary particles constituting the secondary particles, and the positive electrode active material can contain secondary particles with various average major axis lengths.
[0056] Furthermore, when the aforementioned lithium manganese-based oxide is "a non-condensed form of a single primary particle" or "a particle formed by the aggregation of a relatively small number of primary particles", the size (average particle size) of the primary particles contained in "a non-condensed form of a single primary particle" or "a particle formed by the aggregation of a relatively small number of primary particles" can be larger than the size (average particle size) of the primary particles contained in "a secondary particle formed by the aggregation of tens to hundreds or more primary particles".
[0057] For example, when the aforementioned lithium manganese-based oxide is a "non-condensed form of a single primary particle" or a "particle formed by the aggregation of a relatively small number of primary particles," the average major axis length of the primary particles can be in the range of 0.5 μm to 20 μm. On the other hand, when the aforementioned lithium manganese-based oxide is a "particle formed by the aggregation of multiple (tens to hundreds or more) primary particles," the average major axis length of the primary particles can be in the range of 0.1 μm to 5 μm.
[0058] Furthermore, the aforementioned primary particles may include at least one crystallite. That is, the aforementioned primary particles may exist as a single crystallite or as particles containing multiple crystallites.
[0059] The lithium manganese-based oxides defined herein can be represented by the following chemical formula 1.
[0060] [Chemical Formula 1]
[0061] rLi₂MnO₃·(1-r)Li a Ni x Co y Mn z M1 1-(x+y+z) O2
[0062] Herein, M1 is at least one selected from the group consisting of Mo, Nb, Fe, Cr, V, Cu, Zn, Sn, Mg, Ru, Al, Ti, Zr, B, Na, K, Y, P, Ba, Sr, La, Ga, Gd, Sm, W, Ca, Ce, Ta, Sc, In, S, Ge, Si and Bi, 0<r≤0.7, 0<a≤1, 0<x≤1, 0≤y<1, 0<z<1, 0<x+y+z≤1. In this case, preferably, x may be 0.6 or less, and z may be 0.4 or more.
[0063] The lithium-manganese-based oxide represented by the above Chemical Formula 1 may optionally include cobalt. In addition, when the above lithium-manganese-based oxide includes cobalt, the ratio of the number of moles of the above cobalt to the number of moles of all metal elements in the above lithium-manganese-based oxide may be 10% or less, and preferably, may be 5% or less. On the other hand, the lithium-manganese-based oxide represented by the above Chemical Formula 1 may not include cobalt.
[0064] The lithium-manganese-based oxide represented by the above Chemical Formula 1 is a composite oxide in which the oxide of the C2 / m phase represented by Li2MnO3 and the oxide represented by Li a Ni x Co y Mn z M1 1-(x+y+z) O2 of the R3-m phase coexist. In this case, the oxide of the C2 / m phase and the oxide of the R3-m phase may exist in a state of forming a solid solution.
[0065] In addition, in the lithium-manganese-based oxide represented by the above Chemical Formula 1, when r exceeds 0.7, the ratio of Li2MnO3 as the oxide of the C2 / m phase in the above lithium-manganese-based oxide increases excessively, which may lead to a decrease in the discharge capacity of the positive electrode active material.
[0066] In the lithium-manganese-based oxide represented by the above Chemical Formula 1, as the R3-m phase oxide, Li a Ni x Co y Mn z M1 1-(x+y+z) In O2, x representing the nickel content is greater than 0 and equal to or less than 1. Preferably, in order to reduce the occurrence of the cation mixing phenomenon in the above lithium-manganese-based oxide as defined herein, in Li a Ni x Co y Mn z M1 1-(x+y+z) In O2, z representing the nickel content may be greater than 0 and equal to or less than 0.6.
[0067] In the lithium-manganese-based oxide represented by the above Chemical Formula 1, as the R3-m phase oxide, Li a Nix Co y Mn z M1 1-(x+y+z) In O2, z, representing the manganese content, is greater than 0 and less than 1. Preferably, to enable the positive electrode active material, including the lithium manganese-based oxides defined herein, to exhibit higher capacity under high-voltage operating conditions, in Li... a Ni x Co y Mn z M1 1-(x+y+z) In O2, z, representing the manganese content, can be equal to or greater than 0.4 and less than 1.
[0068] As shown in Chemical Formula 1 above, the positive electrode active material according to the present invention comprises a lithium-rich lithium manganese-based oxide containing at least lithium, nickel, manganese and doped metals. By controlling the concentration of the transition metal in the lithium manganese-based oxide in each region, it is possible to mitigate and / or prevent the decrease in stability caused by the excessive presence of lithium and manganese in the lithium manganese-based oxide.
[0069] In one embodiment, when the lithium manganese-based oxide is a secondary particle comprising at least one primary particle, the secondary particle may include M calculated from the average composition of all metal elements in the nucleus. 2 / M 1 And M calculated from the average composition of all metallic elements in the shell 2 / M 1 At least one primary particle that is different from each other.
[0070] The aforementioned lithium manganese-based oxides may refer to "non-condensed particles including single primary particles", "secondary particles formed by the condensation of a relatively small number of primary particles", and / or "secondary particles formed by the condensation of multiple (tens to hundreds or more) primary particles".
[0071] As described above, when the concentrations of any metal elements present in the shell (or surface portion) and the core (or center portion) of a particle are different, the aforementioned particle can be referred to as a core-shell particle. That is, the aforementioned lithium manganese-based oxide is a core-shell particle, and the average composition of all metal elements constituting the aforementioned lithium manganese-based oxide in the aforementioned core and the aforementioned shell can be different.
[0072] The shell can occupy at least a portion of the surface of the core. That is, the shell can be partially present on the surface of the core or it can occupy the entire surface of the core. On the other hand, when the radius of the core-shell particle is r, the thickness of the shell can be from 0.001r to 0.5r.
[0073] In this paper, when the molar number of all metal elements in the above-mentioned lithium manganese-based oxide is M 1 The number of moles of nickel is M. 2At that time, M is calculated from the average composition of all metal elements in the core of the aforementioned lithium manganese-based oxide. 2 / M 1 M, calculated from the average composition of all metallic elements in the shell of the aforementioned lithium manganese-based oxides. 2 / M 1 They can be different from each other.
[0074] Furthermore, it is well known that lithium-rich manganese-based oxides containing excess manganese have lower electrical conductivity compared to NCMs or NCAs containing excess LCO or nickel. Additionally, even in typical NCMs, conductivity decreases with increasing manganese content.
[0075] Various reactions occur on the surface of the above-mentioned types of positive electrode active materials. As the manganese content in the positive electrode active material increases, the charge transfer and / or diffusion of lithium ions on the surface are hindered. This phenomenon can be referred to as a decrease in surface kinetics or surface reaction kinetics.
[0076] As described above, M in the shell of lithium manganese-based oxides as defined herein 2 / M 1 With M in the nucleus 2 / M 1 The differences can thus enhance the surface kinetics of lithium manganese-based oxides. The aforementioned effects can also be achieved through the core and shell of primary particles, secondary particles, microcrystals, and / or single crystals, as described below. 2 / M 1 This is achieved through differences. Additionally, the above effect can also be achieved through M in the core and shell of primary particles, secondary particles, microcrystals, and / or single crystals, as described below. 3 / M 1 Differences are used to achieve this.
[0077] M in the nucleus of the aforementioned primary particle 2 / M 1 And M in the shell of the aforementioned primary particle 2 / M 1 In cases where they differ from each other, and M is within the shell of the aforementioned primary particle. 2 / M 1 M in the nucleus of a particle larger than the aforementioned primary particle 2 / M 1 In such cases, it can further contribute to the improvement of the aforementioned surface dynamics.
[0078] Therefore, by making M in the shell of the aforementioned primary particle 2 / M 1 M in the nucleus of a particle larger than the aforementioned primary particle 2 / M 1 This can mitigate and / or prevent phase transitions caused by the migration of transition metals in the aforementioned lithium manganese-based oxides.
[0079] M in the shell of the aforementioned primary particle 2 / M 1 M in the nucleus of a particle larger than the aforementioned primary particle 2 / M 1 At that time, M can be formed 2 / M 1 The gradient decreases from the shell of the aforementioned primary particle towards the nucleus. When M is formed... 2 / M 1 When the gradient decreases from the shell to the nucleus of the aforementioned primary particle, the abrupt change in the concentration of metallic elements between the shell and the nucleus of the aforementioned primary particle can be reduced.
[0080] That is, M in lithium manganese-based oxides as defined in this paper 2 / M 1 The gradient is not imparted by any oxide physically bonded to the primary and / or secondary particles constituting the aforementioned lithium manganese-based oxide, but rather by the natural concentration gradient of the metal elements constituting the lithium manganese-based oxide. Therefore, M-type precipitation can be prevented in any region of the primary and / or secondary particles constituting the aforementioned lithium manganese-based oxide. 2 / M 1 The rapid changes in the crystal structure can improve the stability of the crystal structure of the aforementioned lithium manganese-based oxides.
[0081] On the other hand, when the aforementioned primary particles exist as particles comprising multiple microcrystals, the concentration of transition metals in the aforementioned microcrystals can also be controlled according to each region.
[0082] Specifically, the aforementioned primary particles may include M calculated from the average composition of all metallic elements in the nucleus. 2 / M 1 And M, calculated from the average composition of all metallic elements in the aforementioned microcrystalline shell. 2 / M 1 At least one microcrystal that is different from each other.
[0083] At this point, in the aforementioned primary particle, there exists M calculated from the average composition of all metallic elements in the nucleus. 2 / M 1 And M, calculated from the average composition of all metallic elements in the aforementioned microcrystalline shell. 2 / M 1 When at least one microcrystal is different from the others, a concentration gradient of transition metal can be formed inside the microcrystal in the same direction as the primary particle.
[0084] In other words, M in the shell of the aforementioned microcrystals 2 / M 1 M in the nucleus larger than the above microcrystals 2 / M 1And can form M 2 / M 1 The gradient decreases from the shell towards the core of the aforementioned microcrystals.
[0085] When the aforementioned primary particles exist as particles comprising multiple microcrystals, M exists within the aforementioned microcrystals. 2 / M 1 The gradient can help stabilize the crystal structure of the aforementioned microcrystals and the primary particles including the aforementioned microcrystals, and improve the electrical conductivity.
[0086] When the aforementioned lithium manganese-based oxide is "a secondary particle formed by the aggregation of a relatively small number of primary particles" and / or "a secondary particle formed by the aggregation of multiple (tens to hundreds or more) primary particles", the aforementioned secondary particles themselves can be core-shell particles with different average compositions of all the metal elements constituting the aforementioned lithium manganese-based oxide in the core and shell.
[0087] In this case, M in the shell of the aforementioned secondary particle 2 / M 1 M in the nucleus of the above-mentioned secondary particles 2 / M 1 And can form M 2 / M 1 The gradient decreases from the shell of the aforementioned secondary particle towards the nucleus. When M exists in the aforementioned secondary particle... 2 / M 1 When the gradient is such that M can selectively exist in the primary particles constituting the secondary particles, M can be present. 2 / M 1 The gradient. That is, when M exists in the above secondary particles. 2 / M 1 When the gradient is not present, even if M is not present in the primary particles that constitute the secondary particles mentioned above, 2 / M 1 The gradient of the transition metal is such that the aforementioned secondary particles are stabilized as bulk particles through the aforementioned transition metal gradient.
[0088] Furthermore, in this paper, when the molar number of all metal elements in the aforementioned lithium manganese-based oxide is M... 1 The number of moles of the doped metal is M 3 At that time, M is calculated from the average composition of all metal elements in the core of the aforementioned lithium manganese-based oxide. 3 / M 1 M, calculated from the average composition of all metallic elements in the shell of the aforementioned lithium manganese-based oxides. 3 / M 1 They can be different from each other. M is calculated by taking the average composition of all metal elements in the core of the aforementioned lithium manganese-based oxides. 3 / M 1M, calculated from the average composition of all metallic elements in the shell of the aforementioned lithium manganese-based oxides. 3 / M 1 The effects that can be different from each other are as described above by making M in the shell 2 / M 1 and M in the nucleus 2 / M 1 They are different but have the same effect.
[0089] When the aforementioned lithium manganese-based oxide is a secondary particle comprising at least one primary particle, M is calculated from the average composition of all metal elements in the nucleus of the aforementioned secondary particle. 3 / M 1 M is calculated from the average composition of all metallic elements in the shells of the aforementioned primary particles and / or secondary particles. 3 / M 1 They can be different from each other.
[0090] In other cases, the aforementioned secondary particles may include M calculated from the average composition of all metallic elements in the nucleus. 3 / M 1 And M calculated from the average composition of all metallic elements in the shell 3 / M 1 At least one primary particle that is different from each other.
[0091] Furthermore, when the aforementioned primary particle exists as a particle comprising multiple microcrystals, the aforementioned primary particle may include M calculated from the average composition of all metallic elements in the nucleus. 3 / M 1 And M calculated from the average composition of all metallic elements in the shell 3 / M 1 At least one microcrystal that is different from each other.
[0092] As shown in the various cases above, when M in the nucleus of the aforementioned microcrystal, the aforementioned primary particle, and / or the aforementioned secondary particle... 3 / M 1 and the M in the shell 3 / M 1 When they are different, M in the particle's shell 3 / M 1 M is preferred to be larger than that in the nucleus of the particle. 3 / M 1 Furthermore, M within the particle's shell 3 / M 1 M in the nucleus of the particle 3 / M 1 At that time, M can be formed 3 / M 1 The gradient decreases from the particle's shell toward the particle's nucleus.
[0093] That is, M formed in lithium manganese-based oxides 3 / M 1 The gradient direction is formed with M formed in lithium manganese-based oxides. 2 / M 1 The gradient directions are the same, and with the formation of M in lithium manganese-based oxides 2 / M 1 and M 3 / M 1 The gradient can mitigate and / or prevent the decrease in stability caused by the excess lithium and manganese in the aforementioned lithium manganese-based oxides.
[0094] On the other hand, apart from the core-shell type lithium manganese-based oxides described herein, in the case of various core-shell type cathode active materials (e.g., NCA / NCM, etc.), the precursors are usually synthesized using aqueous metal solutions with different compositions to make the metal element compositions in the core and shell different or to form a concentration gradient of metal elements between the core and shell.
[0095] However, in the case of lithium manganese-based oxides as defined herein, the M in the core and shell of the final product (lithium manganese-based oxide) can be achieved by coating the hydroxide precursor with nickel and / or cobalt prior to calcination (first heat treatment). 2 / M 1 The difference, therefore, can lead to the formation of M in the direction from the core to the shell. 2 / M 1 The gradient.
[0096] Furthermore, according to another embodiment of the invention, prior to calcination (first heat treatment), instead of coating the hydroxide precursor with nickel and / or cobalt, the dopant metal is present in the lithium manganese-based oxide to achieve the aforementioned concentration of the dopant metal (hereinafter referred to as M). 3 / M 1 (represented), thus enabling the realization of M in the core and shell. 2 / M 1 difference.
[0097] Therefore, positive electrode active materials, including lithium-rich lithium manganese-based oxides according to various embodiments defined herein, can exhibit commercially viable levels of electrochemical properties and stability.
[0098] In another embodiment, at least a portion of the surface of the lithium manganese-based oxide may contain at least one metal oxide represented by the following chemical formula 2.
[0099] [Chemical Formula 2]
[0100] Li b M2 c O d
[0101] Wherein, M2 is selected from at least one of Ni, Mn, Co, Fe, Cu, Nb, Mo, Ti, Al, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, P, Eu, Sm, W, Ce, V, Ba, Ta, Sn, Hf, Ce, Gd, and Nd, 0≤b≤8, 0 <c≤8,2≤d≤13。
[0102] The metal oxide represented by the above chemical formula 2 can be formed by reacting at least a portion of the metal elements (nickel, manganese, cobalt and / or doped metals) constituting the lithium manganese-based oxide with lithium present on the surface of the above lithium manganese-based oxide.
[0103] The aforementioned metal oxides not only reduce lithium-containing impurities (or residual lithium) present on the surface of the aforementioned lithium manganese-based oxides, but also serve as a migration path (diffusion path) for lithium ions, thereby improving the electrochemical properties of the aforementioned lithium manganese-based oxides.
[0104] When the aforementioned lithium manganese-based oxide is a core-shell particle, the aforementioned metal oxide can exist as a single entity with the aforementioned shell.
[0105] Therefore, the aforementioned metal oxides may exist in at least a portion of the surface of the microcrystals, primary particles, and / or secondary particles constituting lithium manganese-based oxides.
[0106] The aforementioned metal oxide can be an oxide formed by complexing lithium with an element represented by M2, or an oxide of M2. For example, the aforementioned metal oxide can be Li. a W b O c Li a Zr b O c Li a Ti b O c Li a Ni b O c Li a Co b O c Li a Al b O c Co b O c Al b O c W b O c Zr b O c or Ti b O cHowever, the examples above are only for ease of understanding, and the metal oxides defined herein are not limited to the examples above.
[0107] Furthermore, the aforementioned metal oxide can be an oxide composed of lithium and at least two elements represented by M2, or further includes an oxide composed of lithium and at least two elements represented by M2. For example, an oxide composed of lithium and at least two elements represented by M2 can be Li a (W / Ti) b O c Li a (W / Zr) b O c Li a (W / Ti / Zr) b O c Li a (W / Ti / B) b O c And so on, but not limited to these.
[0108] Lithium secondary batteries
[0109] According to another aspect of the present invention, a positive electrode can be provided comprising a positive current collector and a positive active material layer formed on the positive current collector. The positive active material layer may comprise lithium composite oxide as the positive active material according to various embodiments of the present invention.
[0110] Therefore, specific details regarding lithium composite oxides will be omitted; the following description will only cover the remaining components not previously mentioned. Furthermore, for convenience, the aforementioned lithium composite oxides will be referred to as the positive electrode active material.
[0111] There are no particular limitations on the aforementioned positive electrode current collector, as long as it does not induce chemical changes in the battery and is conductive. For example, stainless steel, aluminum, nickel, titanium, sintered carbon, or aluminum or stainless steel surfaces treated with carbon, nickel, titanium, silver, etc., can be used. Furthermore, the aforementioned positive electrode current collector typically has a thickness of 3μm to 500μm, and fine irregularities can be formed on the surface of the current collector to improve the adhesion of the positive electrode active material. For example, it can be used in various forms such as thin films, sheets, foils, meshes, porous bodies, foams, and nonwovens.
[0112] The aforementioned positive electrode active material layer can be prepared by coating the aforementioned positive electrode current collector with a positive electrode slurry composition comprising the aforementioned positive electrode active material, a conductive material, and, if desired, a binder.
[0113] In this case, the content of the positive electrode active material relative to the total weight of the positive electrode active material layer can be from 80% to 99% by weight, more specifically from 85% to 98.5% by weight. When the positive electrode active material is included in the above content range, excellent capacity characteristics can be exhibited, but it is not limited thereto.
[0114] The aforementioned conductive materials are used to impart conductivity to the electrodes. In the constructed battery, they can be used without restriction as long as they do not cause chemical changes and possess electronic conductivity. Specific examples include graphite such as natural or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powders or fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives. One or more mixtures of these materials may be used. The total weight of the positive electrode active material layer may range from 0.1% to 15% by weight of the aforementioned conductive materials.
[0115] The aforementioned binder enhances the adhesion between multiple positive electrode active material particles and the bonding force between the positive electrode active material and the current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer (EPDM), sulfonated ethylene propylene diene monomer (EPDM), styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof; one or more mixtures thereof may be used. The binder may comprise 0.1% to 15% by weight of the aforementioned binder relative to the total weight of the positive electrode active material layer.
[0116] In addition to utilizing the aforementioned positive electrode active material, the positive electrode can be prepared according to conventional positive electrode preparation methods. Specifically, it can be prepared by coating a positive electrode slurry composition onto a positive electrode current collector and then drying and calendering it. The positive electrode slurry composition is prepared by dissolving or dispersing the aforementioned positive electrode active material in a solvent and selectively dissolving or dispersing the binder and conductive material in the solvent.
[0117] The solvents mentioned above can be solvents commonly used in this technical field, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and one or a mixture of two or more of them can be used. Considering the coating thickness and preparation yield of the slurry, the amount of the solvent used should be sufficient to dissolve or disperse the positive electrode active material, conductive material, and binder, and to have a viscosity that exhibits excellent thickness uniformity when coated for the preparation of the positive electrode.
[0118] Furthermore, in another embodiment, the positive electrode can also be prepared by casting the positive electrode slurry composition onto a separate support, and then laminating the thin film obtained by peeling off the support onto the positive electrode current collector.
[0119] Furthermore, according to another aspect of the present invention, an electrochemical device including the aforementioned positive electrode can be provided. Specifically, the aforementioned electrochemical device can be a battery, a capacitor, etc., and more specifically, it can be a lithium secondary battery.
[0120] Specifically, the aforementioned lithium secondary battery may include a positive electrode, a negative electrode disposed opposite to the positive electrode, and a separator and electrolyte disposed between the positive electrode and the negative electrode. The positive electrode is the same as described above; therefore, for convenience, a detailed description is omitted. The remaining components not previously described will be explained below.
[0121] The aforementioned lithium secondary battery may optionally include: a battery container for housing the electrode assembly comprising the positive electrode, the negative electrode, and the separation membrane; and a sealing component for sealing the battery container.
[0122] The aforementioned negative electrode may include a negative current collector and a layer of negative active material located on the aforementioned negative current collector.
[0123] There are no particular limitations on the aforementioned negative electrode current collector, as long as it does not induce chemical changes in the battery and has high conductivity. For example, copper, stainless steel, aluminum, nickel, titanium, sintered carbon, copper or stainless steel surfaces treated with carbon, nickel, titanium, silver, etc., and aluminum-cadmium alloys can be used. Furthermore, the aforementioned negative electrode current collector can typically have a thickness of 3μm to 500μm. Similar to the positive electrode current collector, the bonding force of the negative electrode active material can be enhanced by forming fine irregularities on the surface of the current collector. For example, it can be used in various forms such as thin films, sheets, foils, meshes, porous bodies, foams, and nonwovens.
[0124] The aforementioned negative electrode active material layer can be prepared by coating the aforementioned negative electrode current collector with a negative electrode slurry composition comprising the aforementioned negative electrode active material and conductive material, and selectively including a binder as needed.
[0125] As the aforementioned negative electrode active material, compounds capable of reversible lithium insertion and extraction can be used. Specific examples include carbon materials such as artificial graphite, natural graphite, graphitized carbon fibers, and amorphous carbon; and metal compounds capable of alloying with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, or Al alloys; such as SiO₂. β Metal oxides capable of being doped and dedoped with lithium, such as (0 < β < 2), SnO2, vanadium oxide, and lithium vanadium oxide; or composites containing the above-mentioned metal compounds and carbon materials, such as Si-C composites or Sn-C composites, may be used, and one or more mixtures thereof may be used. Furthermore, lithium metal films may also be used as the above-mentioned negative electrode active material. Moreover, both low-crystalline carbon and high-crystalline carbon can be used as carbon materials. Representative low-crystalline carbons are soft carbon and hard carbon, while representative high-crystalline carbons are amorphous, plate-like, flake-like, spherical, or fibrous natural or artificial graphite, condensed graphite, pyrolytic carbon, mesophase pitch-based carbon fiber, meso-carbon microbeads, mesophase pitch, and high-temperature calcined carbons such as petroleum or coal tar pitch-derived cokes.
[0126] Based on the total weight of the negative electrode active material layer, it may contain 80% to 99% of the aforementioned negative electrode active material.
[0127] The aforementioned binder is a component that facilitates the bonding between the conductive material, the active material, and the current collector. Typically, 0.1% to 10% by weight of the binder can be added based on the total weight of the negative electrode active material layer. Examples of such binders include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile rubber, fluororubber, and various copolymers thereof.
[0128] The aforementioned conductive material is a component used to further improve the conductivity of the negative electrode active material. Based on the total weight of the negative electrode active material layer, up to 10% by weight of the aforementioned conductive material can be added, preferably up to 5% by weight. There are no particular limitations on this conductive material as long as it does not induce chemical changes in the corresponding battery and possesses conductivity. For example, graphite such as natural graphite or artificial graphite can be used; carbon black such as acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fiber or metal fiber; metal powders such as fluorinated carbon, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.
[0129] In one embodiment, the aforementioned negative electrode active material layer can be prepared by coating a negative electrode slurry composition onto a negative electrode current collector and drying it. The negative electrode slurry composition is prepared by dissolving or dispersing the negative electrode active material in a solvent and selectively dissolving or dispersing the binder and conductive material in the solvent. Alternatively, the negative electrode slurry composition can be cast onto a separate support, and then a thin film layer obtained by peeling off the support can be pressed onto the negative electrode current collector.
[0130] Furthermore, in another embodiment, the aforementioned negative electrode active material layer can also be prepared by coating a negative electrode slurry composition onto a negative electrode current collector and drying it. The aforementioned negative electrode slurry composition is prepared by dissolving or dispersing the negative electrode active material in a solvent and selectively dissolving or dispersing the binder and conductive material in the solvent. Alternatively, the aforementioned negative electrode slurry composition can be cast onto a separate support, and then a thin film layer obtained by peeling off the support can be pressed onto the negative electrode current collector.
[0131] On the other hand, in the aforementioned lithium secondary battery, the separator membrane is used to separate the negative electrode and the positive electrode and provide a channel for the movement of lithium ions. Any separator membrane commonly used in lithium secondary batteries can be used without limitation. In particular, it is preferable to have low impedance and excellent electrolyte moisture-holding capacity for electrolyte ion movement. Specifically, porous polymer films can be used, for example, porous polymer films prepared using polyolefin polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers, and ethylene / methacrylate copolymers, or laminated structures of two or more layers thereof. Furthermore, conventional porous nonwoven fabrics can also be used, for example, nonwoven fabrics made of high-melting-point glass fibers, polyethylene terephthalate fibers, etc. Moreover, to ensure heat resistance or mechanical strength, separator membranes coated with ceramic components and polymeric substances can also be used, selectively in single-layer or multi-layer structures.
[0132] Furthermore, examples of electrolytes used in this invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes, but they are not limited to these.
[0133] Specifically, the electrolyte may contain organic solvents and lithium salts.
[0134] As the aforementioned organic solvents, any organic solvent capable of mediating the movement of ions participating in the electrochemical reactions of the battery can be used without limitation. Specifically, as the aforementioned organic solvents, ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone, and ε-caprolactone can be used; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; dimethyl carbonate (DMC), diethyl carbonate (DEC), methylethyl carbonate (MEC), ethylmethyl carbonate (EMC), ethylene carbonate (EC), and propyl carbonate (EPC) can be used. Carbonate solvents such as carbonate (PC); alcohol solvents such as ethanol and isopropanol; nitriles such as R-CN (where r is a straight-chain, branched, or cyclic hydrocarbon group with 2 to 20 carbon atoms, which may contain double bonds, aromatic rings, or ether bonds); amides such as dimethylformamide; dioxanes such as 1,3-dioxane; or sulfolane, etc. Among these, carbonate solvents are preferred, and more preferably, a mixture of cyclic carbonates (e.g., ethylene carbonate or propylene carbonate, etc.) with high ionic conductivity and high dielectric constant, and low-viscosity linear carbonate compounds (e.g., ethyl methyl carbonate, dimethyl carbonate, or diethyl carbonate, etc.) that can improve the charge-discharge performance of the battery. In this case, when the cyclic carbonate and the linear carbonate are mixed in a volume ratio of about 1:1 to about 1:9, excellent electrolyte performance can be observed.
[0135] The lithium salts described above can be any compound capable of providing lithium ions for use in lithium secondary batteries, without limitation. Specifically, the lithium salts can be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2, etc. Preferably, the concentration of the lithium salts is used in the range of 0.1M to 2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, thus exhibiting excellent electrolyte performance and enabling efficient movement of lithium ions.
[0136] In addition to the electrolyte components described above, for the purpose of improving battery life characteristics, suppressing battery capacity reduction, and increasing battery discharge capacity, the electrolyte may also contain one or more additives such as halogenated alkylene carbonate compounds like difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glycol dimethyl ether, triammonium hexaphosphate, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolides, ethylene glycol dialkyl ethers, ammonium salts, pyrroles, 2-methoxyethanol, or aluminum trichloride. In this case, the electrolyte may contain 0.1% to 5% by weight of the aforementioned additives relative to its total weight.
[0137] As described above, lithium secondary batteries containing the positive electrode active material of the present invention stably exhibit excellent discharge capacity, output characteristics, and lifespan characteristics. Therefore, they can be used in portable devices such as mobile phones, laptops, and digital cameras, as well as in electric vehicles such as hybrid electric vehicles (HEVs).
[0138] The lithium secondary battery according to the present invention is not particularly limited in shape and can be cylindrical, prismatic, pouch-shaped, or coin-shaped, etc. Furthermore, preferably, the lithium secondary battery can be used not only as a battery cell for powering small devices, but also as a unit battery in medium or large battery modules comprising multiple battery cells.
[0139] According to another aspect of the invention, a battery module comprising the aforementioned lithium secondary battery as a single unit and / or a battery pack comprising the same can be provided.
[0140] The aforementioned battery module or battery pack can be used as a power tool; an electric vehicle, including electric vehicles (EVs), hybrid electric vehicles, and plug-in hybrid electric vehicles (PHEVs); or a power source for one or more medium or large-sized devices in an energy storage system.
[0141] The invention will be described in more detail below by way of examples. However, these examples are intended to illustrate the invention only, and the scope of the invention should not be construed as being limited to these examples.
[0142] Preparation Example 1. Preparation of Positive Electrode Active Material
[0143] Example 1
[0144] (a) Precursor preparation
[0145] In a reactor, a mixed aqueous solution of NiSO4·6H2O and MnSO4·H2O in a molar ratio of 40:60 was added to NaOH and NH4OH and stirred. The reactor temperature was maintained at 45℃, and N2 gas was introduced into the reactor while the precursor synthesis reaction proceeded. After the reaction was complete, the mixture was washed and dehydrated to obtain Ni with an average particle size of 4 μm. 0.4 Mn 0.6 (OH)2 precursor.
[0146] (b) First heat treatment
[0147] The sintering furnace in O2 atmosphere is heated at a rate of 2°C / min, and then the precursor obtained in step (a) is heat-treated for 5 hours while maintaining the temperature at 550°C, followed by furnace cooling.
[0148] (c) Second heat treatment
[0149] A mixture is prepared by mixing the precursor obtained in step (b) in the oxide state with LiOH as a lithium compound (lithium / (metals other than lithium) molar ratio = 1.25) and WO3 at 1.0 mol% relative to all metal elements in the precursor.
[0150] Next, the sintering furnace in O2 atmosphere is heated at a rate of 2°C / min, and then the mixture is heat-treated for 8 hours while maintaining 900°C. The furnace is then cooled to finally obtain a positive electrode active material containing lithium-rich lithium manganese-based oxide with an average particle size of 4μm.
[0151] Example 2
[0152] (a) Precursor preparation
[0153] The nickel manganese hydroxide precursor was prepared in the same manner as in Example 1.
[0154] (b) Precursor coating
[0155] An aqueous solution of CoSO4·7H2O, NaOH, and NH4OH were added to a reactor in which the precursor obtained in step (a) was stirred. At this point, CoSO4·7H2O was weighed to 10 mol% before being added. After the reaction was complete, the mixture was washed and dehydrated, then dried at 150°C for 14 hours to obtain the coated precursor.
[0156] (c) First heat treatment
[0157] The sintering furnace in O2 atmosphere is heated at a rate of 2°C / min, and then the precursor obtained in step (b) is heat-treated for 5 hours while maintaining the temperature at 550°C, followed by furnace cooling.
[0158] (d) Second heat treatment
[0159] The mixture is prepared by mixing the oxide precursor obtained in step (c) with LiOH as a lithium compound (molar ratio of lithium to (metals other than lithium) = 1.25).
[0160] Next, the sintering furnace in O2 atmosphere is heated at a rate of 2°C / min, and then the mixture is heat-treated for 8 hours while maintaining the temperature at 850°C. The furnace is then cooled to finally obtain a positive electrode active material containing lithium-rich lithium manganese-based oxide with an average particle size of 4μm.
[0161] Example 3
[0162] Except for step (d) below, the positive electrode active material is prepared in the same manner as in Example 2.
[0163] (d) Second heat treatment
[0164] A mixture is prepared by mixing the precursor obtained in step (c) in the oxide state with LiOH as a lithium compound (lithium / (metals other than lithium) molar ratio = 1.25) and WO3 at 1.0 mol% relative to all metal elements in the precursor.
[0165] Next, the sintering furnace in O2 atmosphere is heated at a rate of 2°C / min, and then the mixture is heat-treated for 8 hours while maintaining the temperature at 850°C. The furnace is then cooled to finally obtain a positive electrode active material containing lithium-rich lithium manganese-based oxide with an average particle size of 4μm.
[0166] Example 4
[0167] (a) Precursor preparation
[0168] The nickel manganese hydroxide precursor was prepared in the same manner as in Example 1.
[0169] (b) Precursor coating
[0170] An aqueous solution of NiSO4·6H2O, NaOH, and NH4OH were added to a reactor in which the precursor obtained in step (a) was stirred. NiSO4·6H2O was weighed to a concentration of 5 mol% before addition. After the reaction was complete, the precursor was washed and dehydrated, then dried at 150°C for 14 hours to obtain the coated precursor.
[0171] (c) First heat treatment
[0172] The sintering furnace in O2 atmosphere is heated at a rate of 2°C / min, and then the precursor obtained in step (b) is heat-treated for 5 hours while maintaining the temperature at 550°C, followed by furnace cooling.
[0173] (d) Second heat treatment
[0174] The mixture is prepared by mixing the oxide precursor obtained in step (c) with LiOH as a lithium compound (molar ratio of lithium to (metals other than lithium) = 1.25).
[0175] Next, the sintering furnace in O2 atmosphere is heated at a rate of 2°C / min, and then the mixture is heat-treated for 8 hours while maintaining 900°C. The furnace is then cooled to finally obtain a positive electrode active material containing lithium-rich lithium manganese-based oxide with an average particle size of 4μm.
[0176] Example 5
[0177] Except for step (d) below, the positive electrode active material is prepared in the same manner as in Example 4.
[0178] (d) Second heat treatment
[0179] A mixture is prepared by mixing the precursor obtained in step (c) in the oxide state with LiOH as a lithium compound (lithium / (metals other than lithium) molar ratio = 1.25) and WO3 at 1.0 mol% relative to all metal elements in the precursor.
[0180] Next, the sintering furnace in O2 atmosphere is heated at a rate of 2°C / min, and then the mixture is heat-treated for 8 hours while maintaining 900°C. The furnace is then cooled to finally obtain a positive electrode active material containing lithium-rich lithium manganese-based oxide with an average particle size of 4μm.
[0181] Example 6
[0182] Except for step (d) below, the positive electrode active material is prepared in the same manner as in Example 2.
[0183] (d) Second heat treatment
[0184] A mixture is prepared by mixing the precursor obtained in step (b) in the oxide state with LiOH as a lithium compound (lithium / (metals other than lithium) molar ratio = 1.25) and Nb2O5 at 0.5 mol% relative to all metal elements in the precursor.
[0185] Next, the sintering furnace in O2 atmosphere is heated at a rate of 2°C / min, and then the mixture is heat-treated for 8 hours while maintaining the temperature at 850°C. The furnace is then cooled to finally obtain a positive electrode active material containing lithium-rich lithium manganese-based oxide with an average particle size of 4μm.
[0186] Example 7
[0187] Except for step (d) below, the positive electrode active material is prepared in the same manner as in Example 2.
[0188] (d) Second heat treatment
[0189] A mixture is prepared by mixing the precursor obtained in step (c) in the oxide state with LiOH as a lithium compound (lithium / (metals other than lithium) molar ratio = 1.25) and MoO3 at 0.5 mol% relative to all metal elements in the precursor.
[0190] Next, the sintering furnace in O2 atmosphere is heated at a rate of 2°C / min, and then the mixture is heat-treated for 8 hours while maintaining the temperature at 850°C. The furnace is then cooled to finally obtain a positive electrode active material containing lithium-rich lithium manganese-based oxide with an average particle size of 4μm.
[0191] Example 8
[0192] (a) Precursor preparation
[0193] In a reactor, a mixed aqueous solution of NiSO4·6H2O and MnSO4·H2O in a molar ratio of 40:60 was added to NaOH and NH4OH and stirred. The reactor temperature was maintained at 45℃, and N2 gas was introduced into the reactor while the precursor synthesis reaction proceeded. After the reaction was complete, the mixture was washed and dehydrated to obtain Ni with an average particle size of 4 μm. 0.4 Mn 0.6 (OH)2 precursor.
[0194] (b) First heat treatment
[0195] The sintering furnace in O2 atmosphere is heated at a rate of 2°C / min, and then the precursor obtained in step (a) is heat-treated for 5 hours while maintaining 800°C, and then the furnace is cooled.
[0196] (C) Precursor Coating
[0197] An aqueous solution of CoSO4·7H2O, NaOH, and NH4OH are added to a reactor in which the precursor obtained in step (b) is in an oxide state and the mixture is stirred. At this point, CoSO4·7H2O is weighed to 10 mol% before being added. After the reaction is complete, the mixture is washed and dehydrated, then dried at 150°C for 14 hours to obtain the coated precursor.
[0198] (d) Second heat treatment
[0199] The mixture is prepared by mixing the precursor obtained in step (c) with LiOH as a lithium compound (molar ratio of lithium to (metals other than lithium) = 1.25).
[0200] Next, the sintering furnace in an O2 atmosphere was heated at a rate of 2°C / min, and then the mixture was heat-treated for 16 hours while maintaining the temperature at 1,000°C. The furnace was then cooled to finally obtain a positive electrode active material containing lithium-rich lithium manganese-based oxides with an average particle size of 5 μm. At this point, as... Figure 7 As shown, it can be confirmed that the average particle size of the primary particles of the lithium manganese-based oxide contained in the above-mentioned positive electrode active material is greater than the average particle size of the primary particles of the lithium manganese-based oxide contained in the positive electrode active materials according to Examples 1 to 3.
[0201] Comparative Example 1
[0202] (a) Precursor preparation
[0203] In a reactor, a mixed aqueous solution of NiSO4·6H2O and MnSO4·H2O in a molar ratio of 40:60 was added to NaOH and NH4OH and stirred. The reactor temperature was maintained at 45℃, and N2 gas was introduced into the reactor while the precursor synthesis reaction proceeded. After the reaction was complete, the mixture was washed and dehydrated to obtain Ni with an average particle size of 4 μm. 0.4 Mn 0.6 (OH)2 precursor.
[0204] (b) First heat treatment
[0205] The sintering furnace in O2 atmosphere is heated at a rate of 2°C / min, and then the precursor obtained in step (a) is heat-treated for 5 hours while maintaining the temperature at 550°C, and then the furnace is cooled.
[0206] (c) Second heat treatment
[0207] The mixture is prepared by mixing the oxide precursor obtained in step (b) with LiOH as a lithium compound (molar ratio of lithium to (metals other than lithium) = 1.25).
[0208] Next, the sintering furnace in O2 atmosphere is heated at a rate of 2°C / min, and then the mixture is heat-treated for 8 hours while maintaining 900°C. The furnace is then cooled to finally obtain a positive electrode active material containing lithium-rich lithium manganese-based oxide with an average particle size of 4μm.
[0209] Comparative Example 2
[0210] (a) Precursor preparation
[0211] In a reactor, a mixed aqueous solution of NiSO4·6H2O and MnSO4·H2O in a molar ratio of 40:60 was added to NaOH and NH4OH and stirred. The reactor temperature was maintained at 45℃, and N2 gas was introduced into the reactor while the precursor synthesis reaction proceeded. After the reaction was complete, the mixture was washed and dehydrated to obtain Ni with an average particle size of 4 μm. 0.4 Mn 0.6 (OH)2 precursor.
[0212] (b) First heat treatment
[0213] The sintering furnace in O2 atmosphere is heated at a rate of 2°C / min, and then the precursor obtained in step (a) is heat-treated for 5 hours while maintaining 800°C, and then the furnace is cooled.
[0214] (c) Second heat treatment
[0215] The mixture is prepared by mixing the oxide precursor obtained in step (b) with LiOH as a lithium compound (molar ratio of lithium to (metals other than lithium) = 1.25).
[0216] Next, the sintering furnace in an O2 atmosphere was heated at a rate of 2°C / min, and then the mixture was heat-treated for 16 hours while maintaining the temperature at 1,000°C. The mixture was then furnace-cooled to finally obtain a positive electrode active material containing lithium-rich manganese-based oxides with an average particle size of 5 μm. It was confirmed that the average particle size of the primary particles of the lithium manganese-based oxides constituting the above-mentioned positive electrode active material increased similarly to that in Example 8.
[0217] Preparation Example 2. Preparation of Lithium Secondary Batteries
[0218] A positive electrode slurry was prepared by dispersing 90% by weight of each of the positive electrode active materials prepared according to Preparation Example 1, 5.5% by weight of carbon black, and 4.5% by weight of PVDF binder in 30g of N-methyl-2-pyrrolidone (NMP). The above positive electrode slurry was uniformly coated on an aluminum film with a thickness of 15μm and vacuum dried at 135°C to prepare a positive electrode for lithium secondary batteries.
[0219] In contrast to the above positive electrode, lithium foil was used as the counter electrode, and a porous polyethylene membrane (Celgard 2300, thickness: 25 μm) was used as the separation membrane. A button cell was prepared using an electrolyte containing ethylene carbonate and ethyl methyl carbonate in a volume ratio of 3:7 and LiPF6 at a concentration of 1.15 M.
[0220] Experimental Example 1. Metal Element Analysis in Lithium Manganese-Based Oxides
[0221] To confirm the variation in metal element content in the lithium manganese-based oxide prepared according to Preparation Example 1, TEM / EDS analysis was performed. TEM images of the lithium manganese-based oxide were obtained after cross-sectional processing of the lithium manganese-based oxide using FIB.
[0222] Figure 1 Based on the cross-sectional TEM image of the lithium manganese-based oxide contained in the positive electrode active material of Example 1, the distribution of nickel, manganese, and tungsten elements was shown by performing EDS mapping on the cross-section of the lithium manganese-based oxide. Furthermore, Figure 2 In order to pass through Figure 1 EDS analysis was performed on the marked directions in the cross-sectional TEM image to show the curves (line sum spectrum) of the changes in the content of metal elements (nickel, manganese and tungsten) present in lithium manganese-based oxides.
[0223] Reference Figure 1 and Figure 2 It can be confirmed that the lithium manganese-based oxide contained in the positive electrode active material of Example 1 is a secondary particle containing multiple primary particles, and a concentration gradient of nickel, manganese and tungsten is formed in a direction that is approximately perpendicular to the direction from the shell of the secondary particle toward the core.
[0224] As stated above, it can be confirmed that the concentration gradients of nickel, manganese, and tungsten formed in a direction almost perpendicular to the direction from the shell of the secondary particle toward the nucleus are due to M calculated from the average composition of all metallic elements in the nucleus of the primary particle. 2 / M 1 and M 3 / M 1 M is calculated from the average composition of all metallic elements in the shell of a primary particle. 2 / M 1 and M 3 / M 1 It happened because they were different from each other.
[0225] Furthermore, it can be confirmed that the concentration of nickel and tungsten in secondary particles is higher closer to the grain boundary between primary particles.
[0226] Table 1 below shows the concentrations (mol%) of nickel, manganese, and tungsten in the core and shells (shell 1, shell 2) of primary particles. The concentrations (mol%) of nickel, manganese, and tungsten in the core and shells (shell 1, shell 2) of primary particles were calculated using Line EDS spectrum, and the concentrations of nickel, manganese, and tungsten in the entire particle (bulk) were calculated using ICP analysis. Shell 1 corresponds to... Figure 1 The direction indicated in the cross-sectional TEM image is based on the shell of a primary particle located on one side of the region corresponding to the core of the primary particle, and the shell (shell 2) corresponds to the... Figure 1 The direction indicated in the cross-sectional TEM image is the shell of a primary particle located on the other side of the region corresponding to the core of a primary particle.
[0227] Table 1
[0228] Ni 38.2 39.1 64.7 71.6 Mn 60.7 60.7 32.7 26.4 W 1.1 0.2 2.6 2.1
[0229] Reference Figure 2 The results in Table 1 show that M is calculated from the average composition of all metallic elements in the core of a primary particle. 2 / M 1 The value of M is 39.1, calculated from the average composition of all metallic elements in the shells (shell 1, shell 2) of the primary particles. 2 / M 1 The values are 64.7 and 71.6, respectively. Therefore, the M values of the aforementioned lithium manganese-based oxides in the shell are... 2 / M 1 Greater than M in the nucleus 2 / M 1 And it is the formation of M 2 / M 1 A collection of primary particles (secondary particles) whose gradient decreases from the shell towards the nucleus.
[0230] Furthermore, M is calculated from the average composition of all metallic elements in the core of a primary particle. 3 / M 1 M is 0.2, and is calculated from the average composition of all metallic elements in the shells (shell 1, shell 2) of the primary particles. 3 / M 1The values are 2.6 and 2.1 respectively. Therefore, the M values of the aforementioned lithium manganese-based oxides in the shell are... 3 / M 1 Greater than M in the nucleus 3 / M 1 And includes the formation of M 3 / M 1 A primary particle moving from the shell toward the nucleus with a decreasing gradient.
[0231] Figure 3 Based on the cross-sectional TEM image of the lithium manganese-based oxide contained in the positive electrode active material of Example 2, the distribution of nickel, cobalt, and manganese elements was shown by performing EDS mapping on the cross-section of the lithium manganese-based oxide. Furthermore, Figure 4 In order to pass through Figure 3 EDS analysis was performed on the marked directions in the cross-sectional TEM image to show the curves (line sum spectrum) of the changes in the content of metal elements (nickel, cobalt and manganese) present in lithium manganese-based oxides.
[0232] Reference Figure 3 and Figure 4 It can be confirmed that the lithium manganese-based oxide contained in the positive electrode active material of Example 2 is a secondary particle containing multiple primary particles, and a concentration gradient of nickel, cobalt and manganese is formed in a direction that is approximately perpendicular to the direction from the shell of the secondary particle toward the core.
[0233] As stated above, it can be confirmed that the concentration gradients of nickel, cobalt, and manganese formed in a direction almost perpendicular to the direction from the shell of the secondary particle toward the nucleus are due to M calculated from the average composition of all metallic elements in the nucleus of the secondary particle. 2 / M 1 and M 3 / M 1 M is calculated from the average composition of all metallic elements in the shell of the secondary particle. 2 / M 1 and M 3 / M 1 It happened because they were different from each other.
[0234] Furthermore, it can be confirmed that the concentration of nickel in the secondary particles is higher the closer to the outermost edge between them.
[0235] Table 2 below shows the concentrations (mol%) of nickel, cobalt, and manganese in the core and shell of the secondary particles. The concentrations (mol%) of nickel, cobalt, and manganese in the core and shell of the secondary particles were calculated using Line EDS spectrum, while the concentrations of nickel, cobalt, and manganese in the entire particle (bulk) were calculated using ICP analysis. The shell corresponds to... Figure 3The direction indicated in the cross-sectional TEM image is the shell of the secondary particle located on the periphery of the region corresponding to the core of the secondary particle.
[0236] Table 2
[0237] Ni 36.0 33.7 67.9 CO 9.8 5.9 7.7 Mn 54.2 60.3 24.4
[0238] Reference Figure 4 The results in Table 2 show that M is calculated from the average composition of all metallic elements in the core of the secondary particle. 2 / M 1 The value of M is 33.7, calculated from the average composition of all metallic elements in the shell of the secondary particle. 2 / M 1 The value is 67.9. Therefore, the M value of the aforementioned lithium manganese-based oxide in the shell is... 2 / M 1 Greater than M in the nucleus 2 / M 1 And it is the formation of M 2 / M 1 Secondary particles with a decreasing gradient from the shell toward the nucleus.
[0239] Figure 5 Based on the cross-sectional TEM image of the lithium manganese-based oxide contained in the positive electrode active material of Example 3, the distribution of nickel, cobalt, manganese, and tungsten elements was shown by performing EDS mapping on the cross-section of the lithium manganese-based oxide. Furthermore, Figure 6 In order to pass through Figure 5 EDS analysis was performed on the directions marked in the cross-sectional TEM image to show the curves (line sum spectrum) of the changes in the content of metal elements (nickel, cobalt, manganese and tungsten) present in lithium manganese-based oxides.
[0240] Reference Figure 5 and Figure 6 It can be confirmed that the lithium manganese-based oxide contained in the positive electrode active material of Example 3 is a secondary particle containing multiple primary particles, and a concentration gradient of nickel, cobalt, manganese and tungsten is formed in a direction that is approximately perpendicular to the direction from the shell of the secondary particle toward the core.
[0241] As stated above, it can be confirmed that the concentration gradients of nickel, cobalt, manganese, and tungsten formed in a direction almost perpendicular to the direction from the shell of the secondary particle toward the nucleus are due to M calculated from the average composition of all metallic elements in the nucleus of the primary particle. 2 / M 1 and M 3 / M 1 M is calculated from the average composition of all metallic elements in the shell of a primary particle. 2 / M 1 and M 3 / M 1 It happened because they were different from each other.
[0242] Furthermore, it can be confirmed that the concentration of nickel and tungsten in secondary particles is higher closer to the grain boundary between primary particles.
[0243] Table 3 below shows the concentrations (mol%) of nickel, cobalt, manganese, and tungsten in the core and shells (shell 1, shell 2) of primary particles. The concentrations (mol%) of nickel, cobalt, manganese, and tungsten in the core and shells (shell 1, shell 2) of primary particles were calculated using Line EDS special metric, and the concentrations of nickel, cobalt, manganese, and tungsten in the entire particle (bulk) were calculated using ICP analysis. Shell 1 corresponds to... Figure 5 The direction indicated in the cross-sectional TEM image is based on the shell of a primary particle located on one side of the region corresponding to the core of the primary particle, and the shell (shell 2) corresponds to the... Figure 5 The direction indicated in the cross-sectional TEM image is the shell of a primary particle located on the other side of the region corresponding to the core of a primary particle.
[0244] Table 3
[0245] Ni 35.2 36.6 49.4 46.3 CO 9.7 17.6 10.9 11.6 Mn 54.0 45.1 34.8 38.1 W 1.1 0.7 4.8 4.0
[0246] Reference Figure 6 The results in Table 3 show that M is calculated from the average composition of all metallic elements in the core of a primary particle. 2 / M 1 The value is 36.6, calculated from the average composition of all metallic elements in the shells (shell 1, shell 2) of the primary particles. 2 / M 1 The values are 49.4 and 46.3 respectively. Therefore, the M values of the aforementioned lithium manganese-based oxides in the shell are... 2 / M 1 Greater than M in the nucleus 2 / M 1 And includes the formation of M 2 / M 1 A primary particle moving from the shell toward the nucleus with a decreasing gradient.
[0247] Furthermore, M is calculated from the average composition of all metallic elements in the core of a primary particle. 3 / M 1 The value of M is 0.7, and it is calculated from the average composition of all metallic elements in the shells (shell 1, shell 2) of the primary particles. 3 / M 1The values are 4.8 and 4.0 respectively. Therefore, the M values of the aforementioned lithium manganese-based oxides in the shell are... 3 / M 1 Greater than M in the nucleus 3 / M 1 And includes the formation of M 3 / M 1 A primary particle moving from the shell toward the nucleus with a decreasing gradient.
[0248] Furthermore, referring to Figure 6 It can be confirmed that M repeatedly exists between the core and shell 2 (in the region from 0.15 μm to 0.25 μm relative to the line EDS spectrum). 2 / M 1 The gradient. The above results indicate that the lithium manganese-based oxide contained in the positive electrode active material according to Example 3 is a secondary particle containing multiple primary particles. Furthermore, the primary particles comprise multiple microcrystals and form M... 2 / M 1 The gradient decreases from the shell towards the core of the aforementioned microcrystals.
[0249] Tables 4 to 7 below show the results of the determination of the metal element concentration in the core and shell of the primary particles of the lithium manganese-based oxide contained in the positive electrode active materials according to Examples 4 to 7 by Line EDS analysis and ICP analysis, respectively. This confirms that the concentration difference of the metal element between the core and shell is achieved in the same way as in the positive electrode active materials according to the various embodiments described above. Specifically, with the line scanning direction passing through the core of the primary particle as a reference, shell 1 corresponds to the shell of the primary particle located on one side of the region corresponding to the core, and shell 2 corresponds to the shell of the primary particle located on the other side of the region corresponding to the core.
[0250] Table 4
[0251] Ni 42.3 36.8 65.5 56.3 Mn 57.7 63.2 34.5 43.7
[0252] Table 5
[0253] Ni 41.90 38.3 55.7 58.7 Mn 57.09 61.2 40.9 37.1 W 1.01 0.5 3.4 4.2
[0254] Table 6
[0255] Ni 36.0 34.09 47.25 42.9 CO 9.6 10.4 12.1 11.6 Mn 53.8 55.3 38.7 43.4 Nb 0.55 0.21 1.95 2.1
[0256] Table 7
[0257] Ni 36.1 35.5 50.4 44.98 CO 9.6 9.7 10.4 11.1 Mn 53.8 54.7 37.9 43.2 Mo 0.5 0.1 1.3 0.72
[0258] Figure 7Based on the cross-sectional TEM image of the lithium manganese-based oxide contained in the positive electrode active material of Example 8, the distribution of nickel, cobalt, and manganese elements was shown by performing EDS mapping on the cross-section of the lithium manganese-based oxide. Furthermore, Figure 8 In order to pass through Figure 7 The direction marked ① in the cross-sectional TEM image was analyzed by EDS to show the curve (line sum spectrum) of the changes in the content of metal elements (nickel, cobalt, and manganese) present in lithium manganese-based oxides. Figure 9 In order to pass through Figure 7 The direction marked in the cross-sectional TEM image ② was used for EDS analysis to show the curve (line sum spectrum) of the changes in the content of metal elements (nickel, cobalt and manganese) present in lithium manganese-based oxides.
[0259] Reference Figures 7 to 9 It can be confirmed that the crystal size of the lithium manganese-based oxide particles contained in the positive electrode active material according to Example 8 is larger than that of the particles constituting the positive electrode active material as shown in Example 8. Figure 1 , Figure 3 and Figure 5 The crystal size of the lithium manganese-based oxide particles shown. The aforementioned differences can be determined under the first heat treatment conditions, and it can be confirmed that prolonged heat treatment of the hydroxide precursor at a higher temperature promotes crystal growth of the lithium manganese-based oxide particles constituting the positive electrode active material according to Example 8.
[0260] Figure 7 The direction ① shown in the cross-sectional TEM image is used to confirm the concentration changes of metallic elements (nickel, cobalt, and manganese) in the primary particles. Table 8 below shows the concentrations (mol%) of nickel, cobalt, and manganese in the core and shell of the primary particles. The concentrations (mol%) of nickel, cobalt, and manganese in the core and shell of the primary particles were calculated using Line EDS spectrum, and the concentrations of nickel, cobalt, and manganese in the entire particle (bulk) were calculated using ICP analysis. The shell corresponds to... Figure 7 The direction indicated by ① in the cross-sectional TEM image is the shell of the primary particle located on the periphery of the region corresponding to the core of the primary particle.
[0261] Table 8
[0262] Ni 36.7 41.7 57.3 CO 9.6 10.6 9.6 Mn 53.7 47.8 33.1
[0263] Reference Figure 8 The results in Table 8 show that M is calculated from the average composition of all metallic elements in the core of a primary particle. 2 / M 1The value of M is 41.7, calculated from the average composition of all metallic elements in the shell of a primary particle. 2 / M 1 The value is 57.3. Therefore, the M value of the aforementioned lithium manganese-based oxide in the shell is... 2 / M 1 Greater than M in the nucleus 2 / M 1 And includes the formation of M 2 / M 1 A primary particle moving from the shell toward the nucleus with a decreasing gradient.
[0264] Figure 7 Direction ② of the cross-sectional TEM image is used to confirm the concentration changes of metallic elements (nickel, cobalt, and manganese) in the secondary particles. Table 9 below shows the concentrations (mol%) of nickel, cobalt, and manganese in the core and shell of the secondary particles. The concentrations (mol%) of nickel, cobalt, and manganese in the core and shell of the secondary particles were calculated using Line EDS spectrum, and the concentrations of nickel, cobalt, and manganese in the entire particle (bulk) were calculated using ICP analysis. The shell corresponds to... Figure 7 The direction indicated by ② in the cross-sectional TEM image is the shell of the secondary particle located on the periphery of the region corresponding to the core of the secondary particle.
[0265] Table 9
[0266]
[0267]
[0268] Reference Figure 9 The results in Table 9 show that M is calculated from the average composition of all metallic elements in the core of the secondary particle. 2 / M 1 The value of M is 41.4, calculated from the average composition of all metallic elements in the shell of the secondary particle. 2 / M 1 The value is 55.3. Therefore, the M value of the aforementioned lithium manganese-based oxide in the shell is... 2 / M 1 Greater than M in the nucleus 2 / M 1 And includes the formation of M 2 / M 1 Secondary particles with a decreasing gradient from the shell toward the nucleus.
[0269] Reference Figures 7 to 9 The results confirm that the aforementioned lithium manganese-based oxide is M in the shell. 2 / M 1 Greater than M in the nucleus2 / M 1 And includes the formation of M 2 / M 1 Secondary particles of primary particles, or M particles in the shell, are formed by a decreasing gradient from the shell towards the nucleus. 2 / M 1 Greater than M in the nucleus 2 / M 1 And form M 2 / M 1 The secondary particles themselves decrease in gradient from the shell towards the nucleus.
[0270] In other words, M in the shell of the aforementioned lithium manganese-based oxide 2 / M 1 Greater than M in the nucleus 2 / M 1 And form M 2 / M 1 The unit of particles in the gradient decreasing from the shell toward the nucleus can be a primary particle and / or a secondary particle, or it can be a microcrystalline unit that constitutes a primary particle.
[0271] Figure 10 To illustrate the distribution of nickel and manganese elements, EDS mapping was performed on the cross-sectional TEM image of the lithium manganese-based oxide contained in the positive electrode active material of Comparative Example 1, based on the cross-sectional image of the aforementioned lithium manganese-based oxide. Furthermore, Figure 11 In order to pass through Figure 10 EDS analysis was performed on the marked directions in the cross-sectional TEM image to show the curves (line sum spectrum) of the changes in the content of metal elements (nickel and manganese) present in lithium manganese-based oxides.
[0272] Additionally, Table 10 below shows the concentrations (mol%) of nickel and manganese in the core and shell of primary particles. The concentrations (mol%) of nickel and manganese in the core and shell of primary particles were calculated using Line EDSspectrum, and the concentrations of nickel and manganese in the bulk particles were calculated using ICP analysis.
[0273] Table 10
[0274] Ni 38.7 37.9 37.6 Mn 61.3 62.1 62.4
[0275] Reference Figure 10 and Figure 11 It can be confirmed that the lithium manganese-based oxide contained in the positive electrode active material according to Comparative Example 1 is a secondary particle containing multiple primary particles, and no concentration gradient of nickel and manganese is formed between the core and shell of the primary particles existing on the outermost periphery of the secondary particles.
[0276] Table 11 below shows the results of the determination of the concentration of metal elements in the core and shell of the primary and secondary particles of the lithium manganese-based oxide contained in the positive electrode active material according to Comparative Example 2 by Line EDS analysis and ICP analysis. It can be confirmed that, unlike the positive electrode active material according to Example 8 above, there does not seem to be a difference in the concentration of metal elements between the shell and the core.
[0277] Table 11
[0278]
[0279] Experimental Example 2. Evaluation of the Electrochemical Characteristics of Lithium Secondary Batteries
[0280] The lithium secondary battery (button cell) prepared according to Preparation Example 2 was subjected to charge / discharge experiments using an electrochemical analysis apparatus (Toyo, Toscat-3100) at 25°C, a voltage range of 2.0V to 4.6V, and a discharge rate of 0.1C to 5.0C to determine the initial charge capacity, initial discharge capacity, initial reversible efficiency, and rate characteristics (discharge capacity ratio; rate capability; C-rate)).
[0281] In addition, the same lithium secondary battery was subjected to 50 charge / discharge cycles at 25°C and within a driving voltage range of 2.0V to 4.6V at 1C / 1C conditions, and then the ratio of the discharge capacity at the 50th cycle to the initial capacity was measured (cycle capacity retention).
[0282] The results of the above measurements are shown in Tables 12 and 13 below.
[0283] Table 12
[0284]
[0285] Table 13
[0286]
[0287]
[0288] Referring to the results in Tables 12 and 13, it can be confirmed that compared with lithium secondary batteries using the positive electrode active materials according to Comparative Examples 1 and 2, the discharge capacity of lithium secondary batteries using the positive electrode active materials according to Examples 1 to 8 is increased, thereby improving reversible efficiency, cycle capacity retention rate and discharge capacity ratio.
[0289] While the embodiments of the present invention have been described above, those skilled in the art will understand that various modifications and alterations can be made to the present invention by adding, modifying, deleting, or supplementing the constituent elements without departing from the spirit of the present invention as described in the claims, and these modifications and alterations also fall within the scope of the present invention.
Claims
1. A positive electrode active material comprising a lithium-rich lithium manganese-based oxide containing at least lithium, nickel, manganese, and a doped metal, characterized in that the lithium manganese-based oxide comprises excess lithium and manganese. When the molar number of all metal elements in the above lithium manganese-based oxide is M 1 The number of moles of nickel is M. 2 hour, M is calculated from the average composition of all metal elements in the core of the aforementioned lithium manganese-based oxide. 2 / M 1 M, calculated from the average composition of all metallic elements in the shell of the aforementioned lithium manganese-based oxides. 2 / M 1 They are different. The above-mentioned lithium manganese-based oxide is represented by the following chemical formula 1: [Chemical Formula 1] rLi2MnO3·(1-r)Li a Ni x Co y Mr z M1 1-(x+y+z) O2 in, M1 is selected from at least one of Mo, Nb, Fe, Cr, V, Cu, Zn, Sn, Mg, Ru, Al, Ti, Zr, B, Na, K, Y, P, Ba, Sr, La, Ga, Gd, Sm, W, Ca, Ce, Ta, Sc, In, S, Ge, Si, and Bi. 0 <r≤0.7,0<a≤1,0<x≤1,0≤y<1,0<z<1,0<x+y+z≤1, The aforementioned lithium manganese-based oxides are C2 / m phase oxides represented by Li2MnO3 and oxides represented by Li a Ni x Co y Mn z M1 1-(x+y+z) O2 represents a composite oxide in which oxides of the R3-m phase coexist.
2. The positive electrode active material according to claim 1, characterized in that, The aforementioned lithium manganese-based oxide is a secondary particle comprising at least one primary particle. The aforementioned secondary particles include M, calculated from the average composition of all metallic elements in the nucleus. 2 / M 1 And M calculated from the average composition of all metallic elements in the shell 2 / M 1 At least one primary particle that is different from each other.
3. The positive electrode active material according to claim 1, characterized in that, The aforementioned lithium manganese-based oxide is a secondary particle comprising at least one primary particle. M is calculated from the average composition of all metallic elements in the nucleus of the aforementioned secondary particles. 2 / M 1 And M, calculated from the average composition of all metallic elements in the shell of the aforementioned secondary particles. 2 / M 1 They are different from each other.
4. The positive electrode active material according to claim 1, characterized in that, The aforementioned lithium manganese-based oxide is a secondary particle comprising at least one primary particle. The aforementioned primary particles include at least one microcrystal. The aforementioned primary particles include M, calculated from the average composition of all metallic elements in the nucleus. 2 / M 1 And M calculated from the average composition of all metallic elements in the shell 2 / M 1 At least one microcrystal that is different from each other.
5. The positive electrode active material according to claim 1, characterized in that, M in the shell of the above-mentioned lithium manganese-based oxide 2 / M 1 M is greater than that in the core of the above-mentioned lithium manganese-based oxides 2 / M 1 .
6. The positive electrode active material according to claim 5, characterized in that, Formation M 2 / M 1 The gradient decreases from the shell to the core of the aforementioned lithium manganese-based oxide.
7. The positive electrode active material according to claim 1, characterized in that, The aforementioned lithium manganese-based oxides also include doped metals. When the molar number of all metal elements in the above lithium manganese-based oxide is M 1 The number of moles of the doped metal is M 3 hour, M is calculated from the average composition of all metal elements in the core of the aforementioned lithium manganese-based oxide. 3 / M 1 M, calculated from the average composition of all metallic elements in the shell of the aforementioned lithium manganese-based oxides. 3 / M 1 They are different from each other.
8. The positive electrode active material according to claim 7, characterized in that, The aforementioned lithium manganese-based oxide is a secondary particle comprising at least one primary particle. The aforementioned secondary particles include M, calculated from the average composition of all metallic elements in the nucleus. 3 / M 1 And M calculated from the average composition of all metallic elements in the shell 3 / M 1 At least one primary particle that is different from each other.
9. The positive electrode active material according to claim 7, characterized in that, The aforementioned lithium manganese-based oxide is a secondary particle comprising at least one primary particle. M is calculated from the average composition of all metallic elements in the nucleus of the aforementioned secondary particles. 3 / M 1 And M, calculated from the average composition of all metallic elements in the shell of the aforementioned secondary particles. 3 / M 1 They are different from each other.
10. The positive electrode active material according to claim 7, characterized in that, The aforementioned lithium manganese-based oxide is a secondary particle comprising at least one primary particle. The aforementioned primary particles include at least one microcrystal. The aforementioned primary particles include M, calculated from the average composition of all metallic elements in the nucleus. 3 / M 1 And M calculated from the average composition of all metallic elements in the shell 3 / M 1 At least one microcrystal that is different from each other.
11. The positive electrode active material according to claim 7, characterized in that, M in the shell of the above-mentioned lithium manganese-based oxide 3 / M 1 M is greater than that in the core of the above-mentioned lithium manganese-based oxides 3 / M 1 .
12. The positive electrode active material according to claim 11, characterized in that, Formation M 3 / M 1 The gradient decreases from the shell to the core of the aforementioned lithium manganese-based oxide.
13. The positive electrode active material according to claim 1, characterized in that, At least one metal oxide represented by the following chemical formula 2 is present on at least a portion of the surface of the above-mentioned lithium manganese-based oxide: [Chemical Formula 2] Li b M2 c O d in, M2 is selected from at least one of Ni, Mn, Co, Fe, Cu, Nb, Mo, Ti, Al, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, P, Eu, Sm, W, Ce, V, Ba, Ta, Sn, Hf, Gd, and Nd. 0≤b≤8,0 <c≤8,2≤d≤13。 14. A positive electrode, characterized in that, Includes the positive electrode active material according to any one of claims 1 to 13.
15. A lithium secondary battery, characterized in that, Use the positive electrode as described in claim 14.
Citation Information
Patent Citations
Cathode active material, method for preparing the same, and lithium secondary batteries comprising the same
KR1020150069334A
Positive electrode active material for nonaqueous electrolyte secondary batteries, method for manufacturing the same, and nonaqueous electrolyte secondary battery using said positive electrode active material
KR1020140047044A
Positive electrode active material precursor for secondary battery and positive electrode active material for secondary battery prepared by using the same
KR1020180063862A
Positive electrode active material for secondary battery, method of preparing the same, and secondary battery including the positive electrode active material
US20180013129A1